A DEVELOPMENT OF SERBIAN MEDICINE IN THE 19TH CENTURY : - - Meta Jevtovic, Ivana; Djokic, Bojan; Tomovic, Miroslav; Kovacevic, Zoran; Janicijevic, Katarina (Sanamed, 2022)
With the fall of the medieval Serbian state under Turkish rule, every culture, including medicine, died out, and the people resorted to folk medicine and self-taught doctors, i.e. empiricists. Serbs began to get educated in Vienna and Pest, and there were Serbian doctors in Novi Sad already at the beginning of the 18th century. At that time, the first doctors with diplomas appeared in Serbia, but mostly as personal doctors of the Belgrade pasha or Knez Miloš, i.e. his brother Jevrem in Šabac. In the fourth decade of the 19th century, the first military doctors set out, and the newly created four military district commands got their doctors. The Serbian Medical Association started the first medical journal, "Serbian Archives" in 1874. Josif Pancic is writing the first textbook in natural sciences, and Dr. Acim Medovic is writing the first textbook on forensic medicine. Before the First Serbian-Turkish War, the civilian ambulance numbered 69 doctors, 10 medical assistants, 26 pharmacists, and five pharmacy assistants, while the military ambulance had 19 doctors, five medical assistants, one pharmacist, and four pharmacy assistants. Health was initiated but also the establishment of the Ministry of Health and the higher education institution of the Medical Faculty in Belgrade. Guided by the oath, expertise, and experience, the doctors of that time made a significant effort to improve and develop medicine in Serbia in the 19th century.